2022
DOI: 10.3390/ijms231710103
|View full text |Cite
|
Sign up to set email alerts
|

Study of Albumin Oxidation in COVID-19 Pneumonia Patients: Possible Mechanisms and Consequences

Abstract: Oxidative stress induced by neutrophils and hypoxia in COVID-19 pneumonia leads to albumin modification. This may result in elevated levels of advanced oxidation protein products (AOPPs) and advanced lipoxidation end-products (ALEs) that trigger oxidative bursts of neutrophils and thus participate in cytokine storms, accelerating endothelial lung cell injury, leading to respiratory distress. In this study, sixty-six hospitalized COVID-19 patients with respiratory symptoms were studied. AOPPs-HSA was produced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 121 publications
2
15
0
Order By: Relevance
“…High levels of OS suggest a high degree of protein oxidation, structural changes in the protein molecule, the formation of non-functional derivatives, and reduced antioxidant capacity of this critical protein in several COVID-19. Based on our results, we hypothesize that hypoalbuminemia is not only due to the inflammation associated with COVID-19 but rather to oxidative damage, which is also confirmed by other authors [ 51 , 56 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…High levels of OS suggest a high degree of protein oxidation, structural changes in the protein molecule, the formation of non-functional derivatives, and reduced antioxidant capacity of this critical protein in several COVID-19. Based on our results, we hypothesize that hypoalbuminemia is not only due to the inflammation associated with COVID-19 but rather to oxidative damage, which is also confirmed by other authors [ 51 , 56 ].…”
Section: Discussionsupporting
confidence: 91%
“…On the one hand, hyperinflammation in COVID-19 may lead to reduced albumin synthesis and hypoalbuminemia, on the other hand, low albumin levels may result from high clearance of damaged and oxidized albumin [ 56 ]. Based on the obtained CW-EPR data ( Figure 5 ), we hypothesize that in COVID-19 patients, high levels of ROS are the cause of albumin oxidation, the formation of biologically non-functional end products, and the loss of antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been investigated that chlorine compounds produced by activated neutrophils in viral or bacterial infection lead to oxidative modification of albumin and the formation of AOPPs 57,58 . Indeed, the results of our previous study revealed that elevated level of AOPPs is associated with inflammation during the course of COVID-19-related pneumonia 59 . Interestingly, RBCs aggregation was also found to increase in patients with COVID-19 3 .…”
Section: Discussionmentioning
confidence: 85%
“…The different sources of OS in COVID-19 include the generation of free radicals as a protective response to the entry of the virus into the body, an inflammatory response and a cytokine storm accompanied by the production of oxidants leading to the disruption of cellular structures [ 1 , 25 ] and irreversible protein oxidation [ 8 ]. The therapeutics used in the treatment of COVID-19 can exacerbate the pathogenesis of COVID-19, directly increase the risk of intoxication [ 28 ], and disrupt the normal redox balance in the body by mediating the formation of ROS/RNS [ 29 ].…”
Section: Application Of Stable Nitroxide Radical 3-maleimido-proxyl I...mentioning
confidence: 99%
“…In the acute phase of COVID-19, HAS acts as an antioxidant, but high levels of OS can lead to its irreversible oxidation [ 6 , 7 ]. Free radicals (ROS, RNS) are responsible for oxidative damage to HAS, oxidized albumin and low protein level have been implicated in the severity and mortality of patients with SARS-CoV-2 infection [ 8 ]. Badawy et al, reported that hydrogen peroxide and neutrophil-mediated OS induced protein structural and functional changes in patients with COVID-19 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%